Group work and social enterprise: using group members’ skills for social and economic development - Prinsloo, Reineth Christina (Groupwork, 2019)
Poverty is a major issue of concern worldwide and rife in South Africa. Minority groups such as women suffer the most and often have little or no access to opportunities for employment. Social workers have an obligation toward social and economic justice. Although small social enterprises cannot get rid of poverty, it can provide a pathway to address several challenges thereof. This article provides a discussion of a case study from South Africa where a group work project assisted in developing and expanding a social enterprise to combine social and economic development. Group work with its aim of support, growth, mutual aid and cohesion provides an ideal medium to identify, enhance and use the skills and capacities of group members to manage their challenges, and in the process, to enhance their sense of self-worth. It is recommended that social workers need knowledge and skills of entrepreneurship to facilitate the development of sustainable social enterprises. However, multi-stakeholder involvement can assist in the aim of such ventures to work towards sustainability. In this discussion of a case study, and with a strength perspective as foundation, three groups of unemployed individuals were formed that made conference bags and key rings while discussing life issues. Using meso skills can bridge the divide to address macro issues.